The GP's role in promoting winter wellness - Gordon, D; Bone, A; Pebody, R; De Lusignan, S (Royal College of General Practitioners, 2017)
Every year in the UK there is a seasonal peak in morbidity and mortality during the coldest months. GPs have an important role in promoting winter wellness and we would like to advocate GPs placing more emphasis on a proactive approach designed to reduce risk among vulnerable individuals and families. Although some of the activities we already undertake contribute to this goal, others fall short, and few of us promote winter wellness in a coordinated way across our health and social care community. To maximise our effectiveness, primary care teams should be aware of the modifiable risk factors for excess winter mortality and morbidity; and actively manage these as part of planned as well as opportunistic care.